Inhibition of de novo ceramide biosynthesis by FTY720 protects rat retina from light-induced degeneration - Hui Chen; Julie-Thu A. Tran; Annette Eckerd; Tuan-Phat Huynh; Michael H. Elliott; Richard S. Brush; Nawajes A. Mandal (Journal of Lipid Research, 2013)
Light-induced retinal degeneration (LIRD) in albino rats causes apoptotic photoreceptor cell death. Ceramide is a second messenger for apoptosis. We tested whether increases in ceramide mediate photoreceptor apoptosis in LIRD and if inhibition of ceramide synthesis protects the retina. Sprague-Dawley rats were exposed to 2,700 lux white light for 6 h, and the retinal levels of ceramide and its intermediary metabolites were measured by GC-MS or electrospray ionization tandem mass spectrometry. Enzymes of the de novo biosynthetic and sphingomyelinase pathways of ceramide generation were assayed, and gene expression was measured. The dosage and temporal effect of the ceramide synthase inhibitor FTY720 on the LIRD retina were measured by histological and functional analyses. Retinal ceramide levels increased coincident with the increase of dihydroceramide at various time points after light stress. Light stress in retina induces ceramide generation predominantly through the de novo pathway, which was prevented by systemic administration of FTY720 (10 mg/kg) leading to the protection of retinal structure and function. The neuroprotection of FTY720 was independent of its immunosuppressive action. We conclude that ceramide increase by de novo biosynthesis mediates photoreceptor apoptosis in the LIRD model and that inhibition of ceramide production protects the retina against light stress.